Assessing the Financial Soundness of Indonesia's Largest Islamic Bank: An RGEC Framework Analysis - Ismul Aksan; Kasim Sinen; Mahardika Catur Putriwana Malik (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to assess the financial soundness of PT Bank Syariah Indonesia Tbk (BSI) during the pivotal consolidation period from 2020 to 2024. The research specifically evaluates how the mega merger affects the bank's risk capability, efficiency, and overall stability. The assessment utilizes the RGEC method in accordance with Financial Services Authority (FSA) regulations. This quantitative descriptive study analyzes secondary data from BSI’s annual reports over a five-year observation period (2020–2024). The results demonstrate that BSI consistently maintained a Very Healthy composite rating throughout the period. Specifically, the bank showed remarkable improvement in operational efficiency, with BOPO decreasing significantly from 84.61% (2020) to 69.93% (2024), and profitability rising with ROA reaching 2.49% in 2024. Risk management also strengthened, evidenced by a low Net NPF of 0.50% and a robust CAR above 21%. Furthermore, GCG implementation achieved a Very Good predicate in 2024. Practical Implications: The findings suggest that the merger successfully achieved operational synergy without compromising financial stability. The study recommends that management maintain the current efficiency level while exploring further financing expansion given the high liquidity and capital buffer.